Epidemiological profile and quality of life of patients with fibromyalgia in Rheumatology services in Aracaju-SE (Research, Society and Development, 2023)
Fibromyalgia (FM) is a relatively common syndrome characterized by chronic widespread musculoskeletal pain accompanied by various somatic and psychological symptoms. Its prevalence has been estimated to be in the range of 2% to 7%. The vast majority of diagnosed patients are female, white, and middle-aged - around 50 years old. In addition, these patients have alterations in various social and personal aspects that interfere with overall quality of life. Mood changes, complaints of intense fatigue, difficulties sleeping, problems performing common activities and occupations are the main obstacles faced by these patients on a daily basis. This study aimed to provide a better understanding of the profile of fibromyalgia patients and the interference of disease-associated factors on their quality of life. Thus, a cross-sectional and quantitative study was conducted based on the application of a form constructed by the researchers themselves, with the Fibromyalgia Impact Questionnaire (FIQ) validated in Brazil, containing 40 questions, in addition to the questionnaire with sociodemographic and dichotomous variables, and the visual analogue pain scale (VAS). The study included patients from three hospitals in Aracaju-SE, and data were collected through the application of forms during consultations. The collected data were used to determine the epidemiological profile and impact on the quality of life of patients with fibromyalgia. The results of this study provide a better understanding of the profile of fibromyalgia patients and the interference of disease-associated factors on their quality of life.